Slum Dwellers' perception about COVID-19: A Study in Dhaka Metropolis Slums - Mamun, Muhammad; Fatima, Kaniz (Technium Social Sciences Journal, 2021)
This research explored Dhaka slum dwellers’ (n=434 using convenience, quota, and judgmental sampling) view about COVID-19, its causes, preventive measures, potential high-risk groups, self-awareness, transmission prevention, orthodox beliefs, and vaccine effectiveness using 56 simple variables grouped in eight complex variables. The slum dwellers viewed COVID-19 as a fatal and chronic disease spread by Chinese. They perceive that direct contact with infected persons, cough and sneeze droplets, and physical proximity cause the disease. Regarding preventive measures, they think that they must wear masks, frequently wash hands, face, and feet, use soap or hand sanitizer to wash hands. They assume that hot water gargle, more lime/lemon intake, sunlight exposure, and physical activities can reduce the risk of infection. They also perceive that people of any age bear the risk of contagion; but asthmatic, heart and diabetic patients fall in the high-risk group. The slum people self-protect covering nose and mouth while sneeze and cough, take precaution if tested positive, and maintain social distance. They take this disease seriously, as such, they wear masks, avoid guests, friends, and mass transports. They subscribed that if affected they will be in self-quarantine and follow prescribed movement and lockdown decisions to prevent transmission. They believe that home quarantine is for the infected persons only. Slum residents are found to recognize preventive mechanism and self-awareness tactics; but they are carried away by some religious beliefs like the disease is Allah’s will, a curse from Allah, results of our misdeeds, and Allah will save COVID-affected people. Because of their doubt of vaccine effectiveness, they are not quite confident about taking vaccine. Overall, the respondents do not think that they are risk-free. It is found that some of their views are not factual, like COVID-19 is a chronic disease, spread by Chinese; sunrays, hot water gargle reduces risks; lime/lemon intake prevent the disease; or diabetic, asthmatic, and heart patients are at more risks. It is noted that most of the perceptional differences are observed with family types. Nuclear family respondents believe that cold weather causes it and perceive strongly that asthmatic patients are more susceptible to infection. They perceive similar risk of being affected if exposed to a diseased person; however, infected elderly people with comorbidities are more prone to serious illness. They blindly perceive that COVID-19 is all Allah’s will. Education wise, the participants differ in their opinion in almost all the variables. Female slum members firmly believe that Chinese has brought the disease; but males are noted to be more self-aware than females. Married slum residents strongly believe that sunlight exposure and physical activities can prevent the disease and hold the misconception that COVID-19 is a curse from Allah and results of all our misdeeds. Irrespective of their literacy level all respondents believe that Allah will save COVID-affected people. Further, occupation-wise slum dwellers have similar viewpoint about preventing the disease and curbing community transmission. Slum residents’ opinion related to causes of the disease and vaccination has no association with age and income. Older slum residents are found to be more self-aware and cautious in limiting disease transmission, although they possess stronger orthodox religious views and more dubious about vaccination. Slum dwellers’ perception to several aspects of COVID-19 are noticed to be weakly positively related with income, indicating that even when the relatively higher income groups retain views closer to reality, their tendency to be conscious and abide by protective mechanism to reduce risk and control spread of the disease is less as opposed to insolvent slum inhabitants. The factor analysis has found that the grouping variables and the factor variables are quite consistent. It is noted that “self-awareness” and “risk reduction” are the most important factors followed by perception regarding COVID-19 vaccine. In short, slum dwellers are not observed to have a very clear idea about COVID-19, its causes, prevention mechanism, etc. They are aware of some methods of self-protection and deterrence of transmission. However, it is to be ensured that they strictly follow the methods to protect themselves and avoid community spread of the disease.